Iron availability in tropical soils and iron uptake by plants - Mielki, Guilherme Furlan; Novais, Roberto Ferreira; Ker, João Carlos; Vergütz, Leonardus; Castro, Gustavo Franco de (Revista Brasileira de Ciência do Solo, 2015)
Given the increase in crop yields and the expansion of agriculture in low fertility soils, deficiency of micronutrients, such as iron, in plants grown in tropical soils has been observed. The aim of this study was to evaluate Fe availability and Fe uptake by corn (Zea mays L.) plants in 13 different soils, at two depths. Iron was extracted by Mehlich-1, Mehlich-3, and CaCl2 (Fe-CC) and was fractionated in forms related to low (Feo) and high (Fed) crystallinity pedogenic oxyhydroxides, and organic matter (Fep) using ammonium oxalate, dithionite-citrate, and sodium pyrophosphate, respectively. In order to relate Fe availability to soil properties and plant growth, an experiment was carried out in a semi-hydroponic system in which part of the roots developed in a nutrient solution (without Fe) and part in the soil (the only source of Fe). Forty-five days after seeding, we quantified shoot dry matter and leaf Fe concentration and content. Fed levels were high, from 5 to 132 g kg^-1, and Feo and Fe-CC levels were low, indicating the predominance of Fe as crystalline oxyhydroxides and a low content of Fe readily available to plants. The extraction solutions showed significant correlations with various soil properties, many common to both, indicating that they act similarly. The correlation between the Mehlich-1 and Mehlich-3 extraction solutions was highly significant. However, these two extraction methods were inefficient in predicting Fe availability to plants. There was a positive correlation between dry matter and Fe levels in plant shoots, even within the ranges considered adequate in the soil and in the plant. Dry matter production and leaf Fe concentration and content were positively correlated with Fep concentration, indicating that the Fe fraction related to soil organic matter most contributes to Fe availability to plants.
Keywords: Mehlich; Corn (Zea mays); Micronutrient; Nutrient solution; Latossolo